\(x\left(3+x\right)\left(x^2+6\right)=4\left(x^2-4x+4\right)\)
\(3x^3+18x+x^4+6x^2=4x^2-16x+16\)
\(3x^3+18x+x^4+6x^2-4x^2+16x-16=0\)
\(3x^2+34x+x^4+2x^2-16=0\)
=> vô nghiệm
\(x\left(3+x\right)\left(x^2+6\right)=4\left(x^2-4x+4\right)\)
\(3x^3+18x+x^4+6x^2=4x^2-16x+16\)
\(3x^3+18x+x^4+6x^2-4x^2+16x-16=0\)
\(3x^2+34x+x^4+2x^2-16=0\)
=> vô nghiệm
Giải các phương trình sau:
a \(\left(x+2\right)\left(x+\text{4}\right)\left(x+6\right)\left(x+8\right)+16=0\)
b \(\left(x+2\right)\left(x+3\right)\left(x+4\right)\left(x+5\right)-24=0\)
c \(\left(4x+1\right)\left(12x-1\right)\left(3x+2\right)\left(x+1\right)-4=0\)
d \(\left(x^2-3x+2\right)\left(x^2+15x+56\right)+8=0\)
Giải các phương trình sau:
a \(\left(X^2+2x\right)^2-3\left(x^2+2x\right)+2=0\)
b \(\left(x^2+x\right)\left(x^2+x+1\right)-6=0\)
c \(x^4-4x^3+x+3=0\)
d \(x^4-2x^3+x=2\)
giải phương trình :
\(\left(x-2\right)\left(x-1\right)\left(x-8\right)\left(x-4\right)=4x^2\)
Giải các phương trình:
a) (\(x^2-4x\))\(^2\) = 4\(\left(x^2-4x\right)\)
b) \(\left(x+2\right)^2-x+1=\left(x-1\right)\left(x+1\right)\)
Giải các phương trình sau:
a \(x^4-x^2-56=0\)
b \(\left(x-2\right)^4+\left(x+2\right)^4=32\)
c \(\left(x+3\right)^4+\left(x+5\right)^4=16\)
d \(\left(6-x\right)^4+\left(8-x\right)^4=80\)
Giải phương trình: \(\sqrt{\left(x^2+1\right)\left(x+3\right)\left(x^4+5\right)\left(x+7\right)}=\sqrt{\left(x+2\right)\left(x^4+4\right)\left(x+6\right)\left(x^2+8\right)}\)
Giải phương trình \(\left(x+1\right)\left(x+2\right)\left(x+3\right)\left(x+6\right)=\dfrac{-3x^2}{4}\)
Giải Phương Trình
\(\sqrt{\left(2x+3\right)^2}=5\)
\(\sqrt{9\left(x-2\right)^2}=18\)
\(\sqrt{9x-18}-\sqrt{4x-8}+3\sqrt{x-2}=40\)
\(\sqrt{4.\left(x-3\right)^2}=8\)
\(\sqrt{5x-6}-3=0\)
giải phương trình:
\(\left(x^2+4x+1\right)+4\left(x^2+4x+1\right)=x-1\)